Impact of Art Therapy on Non-Verbal Intelligence Quotient and Attention Age among children’s in Cleft Lip and Cleft Palate Patient at Smile Train CLC BMJH - Ms. Ayesha Anjum (International Journal of Indian Psychȯlogy, 2022)
The Psychologist in this study wanted to know the impact of Art Therapy in group of cleft lip/palate children’s who attended Art Therapy Camp at Smile Train- Cleft Leadership Centre BMJH. The data was collected pre and post camp using Draw a Man tool to access non-verbal intelligence quotient and Knox Cube tool to access Attention Age. The researcher has a set sample size of 15 cleft patients who are undergoing treatment in Smile Train Cleft Leadership Centre BMJH. The results indicate there is an impact of Art Therapy in level of Non-Verbal Intelligence Quotient and in level of Attention. It proves art therapy affects the Attention and Intelligence Quotient significantly. The researcher in this study proves that there is a significant difference in level of Non-Verbal IQ and Attention post Art Therapy. Art therapy enriches the life of the cleft child through active art-making, creative process, applied psychological theory, and human experience within a psychotherapeutic relationship.